1998
DOI: 10.14214/sf.695
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing occurrence and impacts of fires in northern European forests

Abstract: The return interval and number of fires vary, depending on the geographical location in interaction with climate, topography and amount of fuel. During recent decades, in northern Europe the number and severity of fires have been insignificant compared with Mediterranean region, in which fire return intervals may be 15-35 years, compared to the average of 60-120 years for boreal forests. This is partly due to the efficient system of fire protection in northern Europe, but is mainly due to the less favourable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Fires affect climate through the change of vegetation structure, surface albedo, and release of aerosols, thus creating a feedback loop (Bowman et al 2009;Bowman et al 2014). In northern Europe, studies have reported strong S-N gradients in the length of fire cycles (Päätalo 1998;Drobyshev et al 2012), likely reflecting forcing of diverse climatic systems on regional fire activity (Drobyshev et al 2012). In the northern part of Sweden, fire activity has been clearly related to variations in Atlantic sea surface temperatures, while in the southern part, this pattern is weakly apparent (Drobyshev et al 2016); hence, fire activity has regional specificity (Drobyshev et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Fires affect climate through the change of vegetation structure, surface albedo, and release of aerosols, thus creating a feedback loop (Bowman et al 2009;Bowman et al 2014). In northern Europe, studies have reported strong S-N gradients in the length of fire cycles (Päätalo 1998;Drobyshev et al 2012), likely reflecting forcing of diverse climatic systems on regional fire activity (Drobyshev et al 2012). In the northern part of Sweden, fire activity has been clearly related to variations in Atlantic sea surface temperatures, while in the southern part, this pattern is weakly apparent (Drobyshev et al 2016); hence, fire activity has regional specificity (Drobyshev et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Biomass and its distribution within forest ecosystems vary with field conditions, e.g., with time since the fire or with fire intensity. At the same time, accumulation of fuel loadings in forest stands is an important determinant of fire frequency and severity (Paatalo, 1998;Cochrane et al, 1999). Therefore, information regarding the nature and distribution of fuels in relation to time elapsed since last fire has been used to project how rapidly fires will spread, their intensity, and ultimately their ecological effects (Rothermel, 1972;Kauffman et al, 1994;Paatalo, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, accumulation of fuel loadings in forest stands is an important determinant of fire frequency and severity (Paatalo, 1998;Cochrane et al, 1999). Therefore, information regarding the nature and distribution of fuels in relation to time elapsed since last fire has been used to project how rapidly fires will spread, their intensity, and ultimately their ecological effects (Rothermel, 1972;Kauffman et al, 1994;Paatalo, 1998). Unlike some southeastern pine forests, where flammable fuels are concentrated on the forest floor and/or in a continuous graminoid layer (Snyder, 1991), most burnable fuels in Florida Keys stands of Pinus elliottii var.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have compared CWD dynamics in different cover types [69]. Differences in DWD dynamics between coniferous forests and TA forests may be induced by the lower pre-fire tree productivity (Figure 2) and the presence of woody debris with higher flammability [83][84][85][86] in coniferous forests.…”
Section: Fuel Load Dynamics With Tsfmentioning
confidence: 99%